Combination with Methotrexate and Cyclophosphamide Attenuated Maturation of Dendritic Cells: Inducing Treg Skewing and Th17 Suppression In Vivo - Xiaoyang Yu; Caihong Wang; Jing Luo; Xiangcong Zhao; Lixing Wang; Xiaofeng Li (Clinical and Developmental Immunology, 2013)
Immune disorder is considered the main pathogenesis of autoimmune diseases, such as rheumatoid arthritis (RA). The balance of the two special subsets of CD4+T cells, T helper cell 17 (Th17), and Regulator T cell (Treg) is the key factor of maintaining a normal immune response. Dendritic cells (DCs), which are the most powerful antigen-presenting cells, play an important role in regulating the balance of Th17 and Treg. The combination of disease modifying antirheumatic drugs (DMARDs) is an important strategy of RA therapy. In this study, we investigated the effect of MTX and CTX on DC maturation in ovalbumin (OVA) immunized mice. Th17 inflammatory response is stronger, while the level of DCs maturity is higher. In contrast, the immunosuppression of Treg is stronger. We found that MTX combined with CTX significantly inhibited the DCs maturity and downregulated the antigen presenting capacity of DCs. As a result, it reestablished a balance of Th17 and Treg. Our study adds a novel mechanism and therapeutic target of MTX combined with CTX for autoimmune disease treatment.